CBP80/20-dependent translation initiation factor (CTIF) inhibits HIV-1 Gag synthesis by targeting the function of the viral protein Rev. Issue 5 (4th May 2021) - García-de-Gracia, Francisco; Gaete-Argel, Aracelly; Riquelme-Barrios, Sebastián; Pereira-Montecinos, Camila; Rojas-Araya, Bárbara; Aguilera, Paulina; Oyarzún-Arrau, Aarón; Rojas-Fuentes, Cecilia; Acevedo, Mónica L.; Chnaiderman, Jonás; Valiente-Echeverría, Fernando; Toro-Ascuy, Daniela; et al.
ABSTRACT: Translation initiation of the human immunodeficiency virus type-1 (HIV-1) full-length RNA has been shown to occur through cap-dependent and IRES-driven mechanisms. Previous studies suggested that the nuclear cap-binding complex (CBC) rather than eIF4E drives cap-dependent translation of the full-length RNA and we have recently reported that the CBC subunit CBP80 supports the function of the viral protein Rev during nuclear export and translation of this viral transcript. Ribosome recruitment during CBC-dependent translation of cellular mRNAs relies on the activity CBP80/20 translation initiation factor (CTIF), which bridges CBP80 and the 40S ribosomal subunit through interactions with eIF3g. Here, we report that CTIF inhibits HIV-1 and HIV-2 Gag synthesis from the full-length RNA. Our results indicate that CTIF associates with HIV-1 Rev through its N-terminal domain and is recruited onto the full-length RNA ribonucleoprotein complex in order to interfere with Gag synthesis. We also demonstrate that CTIF induces the cytoplasmic accumulation of Rev impeding the association of the viral protein with CBP80. We finally show that Rev interferes with the association of CTIF with CBP80 indicating that CTIF and Rev compete for the CBC subunit.